Clinical research in pediatric organ transplantation (Clinics, 2014)
Solid organ transplantation has greatly improved survival in children with end-stage disease, becoming one of the main treatment options in this population. Nonetheless, there are significant challenges associated with validating and optimizing the effects of these interventions in clinical trials. Therefore, we reviewed the main issues related to conducting clinical transplantation research in children. We divided these challenges into three different categories: (i) challenges related to surgical techniques and anesthetic procedures, (ii) challenges related to post-transplant care and (iii) challenges specific to a particular population group and disease type. Some of the observed burdens for clinical research in this field are related to the limitations of conducting studies with a placebo or sham procedure, determining the standard of care for a control group, low prevalence of cases, ethical concerns related to use of a placebo control group and lack of generalizability from animal studies and clinical trials conducted in adult populations. To overcome some of these barriers, it is necessary to utilize alternative clinical trial designs, such as observational studies or non-inferiority trials, and to develop multicenter collaborations to increase the recruitment rate. In conclusion, the lack of robust data related to pediatric transplantation remains problematic, and further clinical trials are needed to develop more efficacious and safer treatments.